Use of Antihelmantic Medicines of A New Type in The Treatment of Moniezois Disease - Chorshambiev Akbar Bozorovich; Bobomurodov Mukhriddin Tursunboyevich; Abdullayev Ozodbek Akbarovich (Scientific Trends, 2024)
Cestodes live as parasites in the gastrointestinal tract of ruminants. Moniesiosis is also a cestode disease that parasitizes the small intestines of sheep and goats. As a result of this disease, animals lose weight, decrease productivity and even die. Currently, many anthelmintics belonging to the albendazole group are being produced for the treatment and prevention of monieziosis.
Keywords: Cestode, moniesiosis, cysticercoid, intermediate host, albendazole, disease biology, anthelmintic, deworming.